1999
DOI: 10.1351/pac199971101829
|View full text |Cite
|
Sign up to set email alerts
|

Environmental applications of low-temperature plasmas

Abstract: Treatment of NO x in diesel engine exhaust represents a big opportunity for the environmental application of low-temperature plasmas. This paper discusses the effect of gas composition on the NO x conversion chemistry in a plasma. It is shown that the plasma by itself cannot chemically reduce NO x to N 2 in the highly oxidizing environment of a diesel engine exhaust. To implement the reduction of NO x to N 2 , it is necessary to combine the plasma with a heterogeneous process that can chemically reduce NO 2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 11 publications
0
82
0
Order By: Relevance
“…Penetrante et al [33] has analyzed this reaction within oxygen rich atmospheric plasma and deduced a reaction efficiency of 10% at 300 o C, whilst the counter reaction (NO 2 → O + NO) is active at greatly elevated temperatures. In this study evidence for this counter reaction is found in the OES spectra of the arc region, thus helping to confirm the ~1700 o C rotational temperature measurements in this region.…”
Section: Real-time Plasma Analysis Oes Measurementsmentioning
confidence: 99%
“…Penetrante et al [33] has analyzed this reaction within oxygen rich atmospheric plasma and deduced a reaction efficiency of 10% at 300 o C, whilst the counter reaction (NO 2 → O + NO) is active at greatly elevated temperatures. In this study evidence for this counter reaction is found in the OES spectra of the arc region, thus helping to confirm the ~1700 o C rotational temperature measurements in this region.…”
Section: Real-time Plasma Analysis Oes Measurementsmentioning
confidence: 99%
“…Among others, the pollutants successfully treated with plasma are acid gases such as NO x , [1][2][3][4][5][6][7] SO x , [6][7][8][9][10] and greenhouse gases such as CO x , [11,12]. Despite successful control in a number of industries, the emitted amounts of volatile organic compounds (VOCs) are still substantial.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that NO 2 reacts with hydrocarbons on a catalyst surface and is de-oxidized to N 2 . Figure 8 shows the gas composition (FT-IR spectra), which shows the effect of a catalyst only, plasma only, and plasma plus catalyst combination on NO X and hydrocarbons [57]. In this case, propene is used as the hydrocarbon reactant.…”
Section: Catalystmentioning
confidence: 99%